The Influence of Entrepreneurial Mindset and Innovation on Startup Growth in the Digital Era - Abdul Rahman, Abdul Wahab; Widiyatmoko, Tri; Rakhmansyah, Mohamad (Startupreneur Business Digital (SABDA Journal), 2025)
This research aims to analyze the influence of entrepreneurial mindset and innovation on startup growth in the digital era. The background to this research is driven by the rapid development of technology which has changed the business landscape, so it is important for startups to have an innovative entrepreneurial mindset and be able to adapt quickly in the face of dynamic market changes. Startups that have a strong entrepreneurial mindset tend to be better able to identify opportunities, take measured risks, and survive in tight market competition. The object of this research is startups operating in the digital sector in Indonesia, with a focus on how entrepreneurial mindset and innovation influence their performance and growth. The method used is a quantitative approach, by distributing questionnaires to startup owners and managers to collect data regarding entrepreneurial mindset, innovation and growth. The collected data was analyzed using linear regression to test the relationship between these variables. The research results show that both entrepreneurial mindset and innovation have a significant positive influence on startup growth, with innovation acting as a mediator that strengthens this relationship. The conclusion of this research is that to achieve sustainable growth, startups need to develop an entrepreneurial mindset that supports creativity and innovation in every aspect of their operations. This research provides insight for startup players in optimizing their business development strategies in the digital era.